Dynamics of Chinese Muslim Development in Medan City, 1965-1998 - Siregar, Rahmad Husein; Syam, Abdi Mubarak (Riwayat: Educational Journal of History and Humanities, 2025)
This research examines the dynamics of Chinese Muslim development in Medan City in the period 1965-1998. Using the historical method and literature review approach, this research analyzes the development and changes that occurred in the Chinese Muslim community in Medan during the New Order period. The results show that the position and role of Chinese Muslims underwent significant changes during the period, from post-G30S/PKI stigmatization to a more positive portrayal of their contributions in the social, economic and religious fields. The formation of the Persatuan Islam Tionghoa Indonesia (PITI) in 1961 and its transformation into Pembina Iman Tauhid Indonesia in 1972 were important milestones in the development of this community. Despite facing various challenges such as discrimination and negative stereotypes, Chinese Muslims in Medan managed to build their dual identity as Muslims and Chinese through a complex process of cultural assimilation and social interaction. This research reveals that the socio-political dynamics of the period affected the public perception and integration process of the Chinese Muslim community into the wider Medan society.